Biocontrol potential and comparative genomic analysis of two Bacillus velezensis strains against sclerotinosis in mulberry fruit - Peng, Fangfang; Li, Xunlan; Wei, Zhaoxin; Han, Guohui (Frontiers in Microbiology, 2025)
Mulberry trees (Morus spp.), a dual-purpose crop with nutritional and medicinal value, faces significant production constraints due to sclerotinosis. Two strains of Bacillus velezensis (JT-3 and JD-3) were isolated, demonstrating strong inhibitory effects against the sclerotinia pathogen (56.06% for JT-3 and 75.42% for JD-3). These strains effectively suppressed sclerotium formation and germination, achieving a complete inhibition rate. Field trials and growth promotion experiments showed that disease incidence in mulberry fruit could be reduced by up to 75.72%, with significant improvements observed in plant height, stem thickness, leaf number, root length, root weight, and above-ground biomass compared to the control group. Oxford Nanopore Technologies (ONT) sequencing showed the genome of JT-3 consists of a single circular chromosome with a size of 3.85 Mb, while the genome of JD-3 comprises a circular chromosome and a plasmid, with a total size of 4.12 Mb, including a plasmid of 35.7 kb. Both strains exhibit the capacity to secrete antifungal Carbohydrate-Active Enzymes (CAZymes) such as lysozyme and chitinase. Comparative genomics identified JD-3-specific enrichments in flagellar motility, hydrolase systems, antimicrobial defense clusters. Additionally, Both strains harbored 12 The biosynthetic gene clusters (BGCs), with JD-3 uniquely encoding plantazolicin synthesis. These findings provide foundational insights for developing Bacillus-based bioformulations while opening new avenues for the health management of mulberry fruit.